Insect Life Cycle Modeling (ILCYM) software a new tool for Regional and Global Insect Pest Risk Assessments under Current and Future Climate Change Scenarios - Sporleder, M.; Tonnang, Henri E.Z.; Carhuapoma, Pablo; González, J.C.; Juarez, H.; Kroschel, Jürgen (CAB International, 2013)
This chapter describes the application of ILCYM (Insect Life Cycle Modelling) software, which supports the development of process-oriented temperature-driven and age-stage structured insect phenology/population models. ILCYM interactively leads the user through the steps for developing insect phenology models, for conducting simulations, and for producing potential population distribution and risk mapping under current or future temperature (climate change) scenarios. The phenology model developed for the potato tuber moth Phthorimaea operculella (Lepidoptera: Gelechiidae) is used to demonstrate the resulting modelling outputs.